2017
DOI: 10.1002/ijgo.12310
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of nonpharmacological adjuvant interventions for patients undergoing assisted reproductive technology treatment

Abstract: Nonpharmacological interventions could improve the psychological outcomes of patients undergoing ART treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…a possible alteration of the regulation of sex hormone signaling, leading to reduction of the reproductive potential (8), thus it has been suggested that increased psychological distress might be linked to reduced pregnancy rates (9,10). Therefore, several studies have examined possible associations between psychosocial interventions focusing on psychological distress and ART treatment outcomes (10)(11)(12)(13)(14)(15)(16)(17), however, the results are equivocal. This systematic review and meta-analysis aim to investigate the effect of psychosocial interventions on pregnancy rates in women or couples undergoing ART treatment compared to pregnancy rates in women or couples undergoing ART treatment and not receiving psychosocial interventions.…”
Section: Introductionmentioning
confidence: 99%
“…a possible alteration of the regulation of sex hormone signaling, leading to reduction of the reproductive potential (8), thus it has been suggested that increased psychological distress might be linked to reduced pregnancy rates (9,10). Therefore, several studies have examined possible associations between psychosocial interventions focusing on psychological distress and ART treatment outcomes (10)(11)(12)(13)(14)(15)(16)(17), however, the results are equivocal. This systematic review and meta-analysis aim to investigate the effect of psychosocial interventions on pregnancy rates in women or couples undergoing ART treatment compared to pregnancy rates in women or couples undergoing ART treatment and not receiving psychosocial interventions.…”
Section: Introductionmentioning
confidence: 99%
“…21 Another covariate that may have significantly increased heterogeneity is the different cultural background of the participants, since the studies originated from countries with cultural differences, hence different perceptions of infertility and its psychosocial repercussion. 50,51 The meta-analysis of Chu et al 52 examined 34 studies, with pre-post design, evaluating the impact of specific non-pharmaceutical psychosocial interventions on anxiety, stress of infertility, depression and pregnancy rates following ART. Twenty-five studies reported on the pregnancy outcome and the interventions included were acupuncture, psychological support and improvement of lifestyle.…”
Section: Resultsmentioning
confidence: 99%
“…This imposes a challenge for the mental health practitioner as research in recent years has failed to establish a clear methodology due to mixed results. For example, some meta-analyzes (Ying et al, 2016;Chu et al, 2017) have suggested that psychological interventions lead to a significant reduction in negative affect caused by infertility, help increase the likelihood of becoming pregnant, and improve marital function ( Frederiksen et al, 2015). On the other hand, there have been meta-analyzes that have indicated the lack of significant effects of psychological interventions on the chance of becoming pregnant and on the decrease in stress levels (Boivin, 2003).…”
Section: Psychological Intervention Strategies For Patients With Infertility -Opportunities and Challengesmentioning
confidence: 99%